Inhibition of HCN channel activity in the thalamus attenuates chronic pain in rats. (19th September 2016) - Ding, Weihua; You, Zerong; Shen, Shiqian; Chen, Lucy; Zhu, Shengmei; Mao, Jianren
Highlights: Inhibition of HCN channel activity in the VPL nucleus of the thalamus attenuated chronic pain. HCN1 and HCN2 protein expression levels were increased in the thalamus under chronic pain condition. Increased HCN channel activity in the thalamus contributed to the maintenance of chronic pain. Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels regulate neuronal excitability in both peripheral and central nerve systems. Emerging evidence indicates that HCN channels are involved in the development and maintenance of chronic pain. However, the impact of HCN channel activity in the thalamus on chronic pain has not been examined. In this report, we evaluated the effect on nociceptive behaviors after infusion of a HCN channel blocker ZD7288 into the ventral posterolateral (VPL) nucleus of the thalamus in rats with neuropathic pain or monoarthritis. We show that ZD7288 dose-dependently attenuated mechanical allodynia and thermal hyperalgesia in rats with chronic pain. In the thalamus, immunoreactivity of both HCN1 and HCN2 subunits was increased in both rat models. These results suggest that the increased HCN channel activity in the thalamus of the ascending nociceptive pathway contributes to both chronic neuropathic and inflammatory pain conditions.